Influence of transport properties on energy resolution of planar TlBr and CdZnTe gamma-ray detectors: Monte-Carlo investigation - Skrypnyk, A.I.; Khazhmuradov, M.A. (Вопросы атомной науки и техники, 2014)
The response of TlBr- and CdZnTe-detectors to gamma-rays from ⁵⁷Со and ¹³⁷Cs was simulated by Monte-Carlo
method via Geant4 package. We studied the influence of transport parameters of electrons and holes on energy
resolution of detectors. The modification of photopeaks with a changing the ratio of the electron and hole mobilitylifetime
products was investigated. All results obtained for TlBr detectors were compared with the results for
CdZnTe-detectors. The efficiency for detecting gamma-quanta in the range of energies from 10 keV to 3 MeV by
both kinds of detector was researched. С помощью пакета Geant4 методом Монте-Карло промоделирован отклик TlBr- и CdZnTe-детекторов на
гамма-излучение от ⁵⁷Со и ¹³⁷Cs . Изучено влияние транспортных свойств электронов и дырок на
энергетическое разрешение детекторов. Исследована модификация фотопиков с изменением отношения
произведений подвижности на время жизни для электронов и дырок. Все результаты, полученные для TlBr-детекторов, были сравнены с результатами для CdZnTe-детекторов. Исследована эффективность обеих
систем детектирования гамма-квантов в диапазоне энергий от 10 кэВ до 3 МэВ. За допомогою пакета Geant4 методом Монте-Карло було промодельовано відгук TlBr- і
CdZnTe-детекторів на гамма-випромінювання від ⁵⁷Со і ¹³⁷Cs. Вивчено вплив транспортних параметрів
електронів і дірок на енергетичну роздільність детекторів. Досліджено модифікацію фотопіків зі зміною
відношення добутків рухливості на час життя для електронів і дірок. Всі результати, які було отримано для
TlBr-детекторів, було порівняно з результатами для CdZnTe-детекторів. Досліджено ефективність обох
систем детектування гамма-квантів у діапазоні енергій від 10 кеВ до 3 МеВ.